2014
DOI: 10.11622/smedj.2014155
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Kienböck’s disease in twelve cases: a mid-term follow-up study

Abstract: METHODSA total of 12 patients (9 male and 3 female) with Kienböck's disease were included in the present case series.The mean age of the 12 patients was 28 years. One patient presented in Lichtman stage I, five in Lichtman stage II, five in Lichtman stage IIIa, and one in Lichtman stage IV. Univariate and multivariate analyses of the obtained data were performed to identify any correlations. RESULTSThe mean follow-up time was 62 months, and the mean modified Mayo wrist score improved from the preoperative valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…It is characterized by lunate sclerosis, cystic changes, fragmentation and articular surface collapse on plain radiograph [3,4]. It occurs most commonly in men aged 20 to 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by lunate sclerosis, cystic changes, fragmentation and articular surface collapse on plain radiograph [3,4]. It occurs most commonly in men aged 20 to 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Various standard modalities are used to treat this disease, including nonsurgical management, vascularised bone graft (VBG), joint levelling procedures, intercarpal arthrodesis, proximal row carpectomy and total wrist arthrodesis [8,9]. Gupta et al in 2014 presented their experience in 12 patients and found improvement in the functional outcome after treatment [3]. Our study aims to determine the functional and radiological outcome after surgery for Kienbock's disease.…”
Section: Introductionmentioning
confidence: 99%